Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0734371x13511087
|View full text |Cite
|
Sign up to set email alerts
|

Is Contracting Out Good or Bad for Employees? A Review of International Experience

Abstract: The past decades have witnessed an upsurge in governments' use of contracting out as a means of reforming and privatizing public service delivery. This development has to a large extent been driven by efficiency and cost-effectiveness concerns, but may also result in important changes in the working conditions and work environment for the personnel in public organizations. In this article, we present the findings from a systematic review of studies documenting the consequences of contracting out for employees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 40 publications
(141 reference statements)
6
86
0
1
Order By: Relevance
“…Johansson (2008) concludes that " [it] is … shown that larger municipalities situated in metropolitan areas use external suppliers to a greater extent" (p. 258), a conclusion supported by Levin and Tadelis (2010). Larger municipalities seem to attract contractors, or be more likely to engage in tendering processes, compared to smaller municipalities (Kjaer Foged, 2016;Vrangbaek et al, 2013).…”
Section: Expectation 2: Is Contracting Out Dependent On Municipal Andmentioning
confidence: 80%
See 1 more Smart Citation
“…Johansson (2008) concludes that " [it] is … shown that larger municipalities situated in metropolitan areas use external suppliers to a greater extent" (p. 258), a conclusion supported by Levin and Tadelis (2010). Larger municipalities seem to attract contractors, or be more likely to engage in tendering processes, compared to smaller municipalities (Kjaer Foged, 2016;Vrangbaek et al, 2013).…”
Section: Expectation 2: Is Contracting Out Dependent On Municipal Andmentioning
confidence: 80%
“…Therefore, continuity and the time dimension are also of theoretical importance, neither of which are discussed further here. The critical stance of marketization theory relies on the assumption that the public sector is driven by value systems that are different to those in the private sector, assuming that the qualities of their activities are worlds apart (Helby Peterson and Hjelmar, 2013;Vrangbaek et al, 2013). From these somewhat opposing approaches to contracting out, we aim to test the extent to which the data at hand responds to the theoretical expectations.…”
Section: The Contracting Out Criticismmentioning
confidence: 99%
“…Our study also provides evidence of the potentially conflicting evaluation of key outcomes. All told, while contracting out has been associated with negative outcomes for employees (Vrangbaek et al, 2015), several public managers indicated that being released from internal staff management responsibilities was a positive outcome and improved the managerial focus (e.g. on more user-oriented core tasks).…”
Section: Discussionmentioning
confidence: 99%
“…O'Flynn and Alford (2008 highlighted a dilemma between the requirements to separate organisational responsibilities and those for accessing sufficient knowledge for well-working contract management as one key outcome for public management. Likewise, the employees in public-service-providing organisations have been found to be impacted significantly by the implementation of contracting out by, for example, adverse changes in employment rates and terms (Vrangbaek et al, 2015. The impact of contracting has also been discussed from the viewpoint of broader governance perspectives.…”
Section: Public Managers and Contracting Outcomes Revisitedmentioning
confidence: 99%
See 1 more Smart Citation